Local regulations on alternative water sources: Greywater and rainwater use in the Metropolitan Region of Barcelona - Domènech, Laia; Vallès, Maria (Universidad de Alicante Servicio de Publicaciones, 2014)
Alternative water resources are gaining momentum in Catalonia (north-east Spain) in an effort to promote water conservation and build resilience against drought episodes. Since 2002 more than 50 municipalities (summing up more than 1.3 million people) have approved a water saving ordinance that involves the installation of rainwater harvesting and/or greywater reuse systems in new buildings. These new technologies trigger important transformations in the existing water cycle including institutional and social changes related with water decentralization. Drawing on interviews with local environmental managers and survey data from rainwater harvesters and greywater users, this paper analyses the social and technical learning generated during the implementation of the regulations and the main impediments and barriers that need to be overcome to control health risks and promote social acceptance of these alternative water sources.